Detection and molecular characterization of uncommon rotavirus group A genotype G12 among hospitalized children in Chennai - Ponnambalam Arun; Kaveri Krishnasami; Palani Gunasekeran; Gracy Fathima; Vidya Padmanabhan (The Turkish Journal of Pediatrics)
Human group A (RVAs) possess genetic diversity and often newer RVA strains have been reported frequently with different G and P combinations worldwide. As the disease burden is more common in low income countries including India, monitoring and detection of the circulating strains of rotavirus needs to be monitored to understand the genetic diversity of the strains which evolve over time. This study was an attempt to provide data on rotavirus gastroenteritis prevalence in and around Chennai Tamilnadu-South India during the pre-vaccination era. Stool samples were collected and tested from 401 children less than five years of age admitted to hospitals with acute gastroenteritis. The samples were subjected to amplification for VP7 and VP4 genes by using consensus primers, followed by semi-nested type-specific multiplex PCR. Phylogenetic analysis of VP7 genes of G12 were carried out and the variations between strains isolated globally were documented. Rotavirus was detected in 167 (41.64%) samples and five were found to be the uncommon G12P[6] genotype (2.99%) tested by RT-PCR followed by G1P[8], G9P[4], G9 with P untypable and G3P[8] and combinations of G2G9P[6] and G9G2P[11] with few strains untypable. In this study we highlight the occurrence of uncommon G12P[6] strain of rotavirus infection in the community. Since rotavirus is transmitted through oral-fecal route and monitoring of environmental cleanliness is mandatory to cease the spread of this deadliest viral agent to achieve our MDG-IV. Covering single genotype will have to be modified with respect to the circulating stains.